Presence of immune cells, low tumor proliferation and wild type BRAF mutation status is associated with a favourable clinical outcome in stage III cutaneous melanoma - Falkenius, Johan (BMC Cancer, 2017)
BACKGROUND: The variable prognosis in stage III cutaneous melanoma is partially due to unknown prognostic factors. Improved prognostic tools are required to define patients with an increased risk of developing metastatic disease who might benefit from adjuvant therapies. The aim was to examine if cellular immune markers in association with tumor proliferation rate and BRAF mutation status have an impact on prognosis in stage III melanoma. METHODS: We have used two sets of case series with stage III disease: 23 patients with short survival (≤ 13 months) and 19 patients with long survival (≥ 60 months). Lymph node metastases were analyzed for Ki67, CD8 and FOXP3 protein expression using immunohistochemistry. BRAF mutation status was analyzed in a previous study on the same samples. RESULTS: Low tumor proliferation rate was significantly associated with a better prognosis (p = 0.013). Presence of FOXP3+ T cells was not correlated to adverse clinical outcome. A highly significant trend for a longer survival was found in the presence of an increasing number of markers; CD8+ and FOXP3+ T cells, low tumor proliferation and BRAF wildtype status (p = 0.003). Presence of at least three of these four markers was found to be an independent favorable prognostic factor (OR 19.4, 95% CI 1.9-197, p = 0.012), when adjusting for ulceration and number of lymph node metastases. Proliferation alone remained significant in multivariate analyses (OR 26.1, 95% CI 2.0-344, p = 0.013) but with a wider confidence interval. This panel still remained independent when also adjusting for a previously identified prognostic glycolytic-pigment panel. CONCLUSIONS: We have demonstrated that presence of immune cells in association with tumor proliferation and BRAF mutation status may further contribute to identify stage III melanoma patients with high risk of relapse.